Atypical Teratoid/Rhabdoid Tumor (AT/RT) Arising From Ependymoma: A Type of AT/RT Secondarily Developing From Other Primary Central Nervous System Tumors. Issue 2 (February 2016) - Nobusawa, Sumihito; Hirato, Junko; Sugai, Tsutomu; Okura, Naoki; Yamazaki, Tatsuya; Yamada, Seiji; Ikota, Hayato; Nakazato, Yoichi; Yokoo, Hideaki
Abstract : Atypical teratoid/rhabdoid tumors (AT/RT) are rare, aggressive, embryonal brain tumors that occur most frequently in very young children; they are characterized by rhabdoid cells and loss of INI1 protein nuclear expression. Here, we report the case of a 24-year-old man with a left frontal lobe tumor that was composed mainly of rhabdoid cells showing loss of INI1 nuclear reactivity and polyphenotypic immunohistochemical expression, with a small INI1-positive component of ependymoma. Array comparative genomic hybridization separately conducted for each histologically distinct component revealed 22 shared identical copy number alterations, including loss of heterozygosity of chromosome 22q containing the INI1 locus. Furthermore, we found the C11orf95-RELA fusion gene, the genetic hallmark of supratentorial ependymomas, not only in the ependymoma component but also in the AT/RT component by fluorescence in situ hybridization analysis, suggesting that the AT/RT cells secondarily progressed from the preexisting ependymoma cells. A second genetic inactivating event in the INI1 gene was not detected in the AT/RT component. There are several reported cases of AT/RT (or INI1-negative rhabdoid tumors) arising in the setting of other primary brain tumors (gangliogliomas, pleomorphic xanthoastrocytomas, and high-grade gliomas), but the present case is the first reported AT/RT apparently evolving from an ependymoma.